Eksplorasi Chat Generative Pre-trained Transformer dalam Perspektif Mahasiswa Pendidikan Akuntansi - Muhammad Karin Pramesti; Asri Diah Susanti (Universitas Sebelas Maret, 2024)
AbstractThis study aimed to: (1) understand accounting education students' perceptions regarding ChatGPT features; (2) understand accounting education students' perceptions regarding the use of ChatGPT in learning accounting and writing articles; (3) understand accounting education students' perceptions regarding the advantages and disadvantages of ChatGPT. This research was a qualitative narrative study. The informants in this study were Accounting Education students from Universitas Sebelas Maret. The sampling technique used in this study was purposive sampling. Data collection was conducted through in-depth interviews. The data validity testing technique used was triangulation method. Data analysis was conducted using interactive analysis. The results of this study were as follows. First, the ChatGPT features frequently used included answering questions, assisting with learning, summarizing information, creating questions or tests, visualizing ideas, and making PowerPoint presentations. Second, the use of ChatGPT in accounting education was considered effective in helping with the understanding of complex material and in finding resources to enrich references. Third, according to the students, the advantages of ChatGPT included its speed in answering questions, easy-to-understand language, and uncomplicated navigation. The disadvantages are that it requires specific commands to get specific answers and unknown sources of answers, making them unverifiable.Keyword: ChatGPT, student perception, accounting education, narrative qualitative. AbstrakPenelitian ini bertujuan untuk: (1) memahami persepsi mahasiswa terkait fitur-fitur ChatGPT; (2) memahami persepsi mahasiswa terkait pemanfaatan ChatGPT dalam pembelajaran akuntansi dan penulisan artikel ilmiah; (3) memahami persepsi mahasiswa pendidikan akuntansi terkait kelebihan dan kekurangan ChatGPT. Penelitian ini merupakan penelitian kualitatif naratif. Informan dalam penelitian ini adalah Mahasiswa Pendidikan Akuntansi, Universitas Sebelas Maret. Teknik pengambilan sampel yang digunakan dalam penelitian adalah purposive sampling. Pengumpulan data dilakukan dengan teknik wawancara mendalam. Teknik uji validitas data yang digunakan adalah triangulasi metode. Analisis data menggunakan analisis interaktif. Hasil penelitian ini adalah sebagai berikut. Pertama, fitur-fitur ChatGPT yang sering digunakan antara lain yaitu, menjawab pertanyaan, asisten belajar, meringkas informasi, membuat soal-soal atau pertanyaan, memvisualisasikan ide, hingga membuat powerpoint. Kedua, penggunaan ChatGPT dalam pembelajaran akuntansi dianggap efektif dalam membantu pemahaman materi yang kompleks dan pencarian materi untuk memperkaya referensi. Ketiga, kelebihan ChatGPT menurut mahasiswa antara lain sangat cepat dalam menjawab pertanyaan, bahasa yang mudah dipahami, dan navigasi yang tidak rumit. Kekurangannya yaitu memerlukan perintah yang spesifik untuk mendapatkan jawaban yang spesifik dan sumber jawaban yang tidak diketahui sehingga tidak dapat dipertanggungjawabkan.Kata kunci: ChatGPT, persepsi mahasiswa, pembelajaran akuntansi, kualitatif naratif.